SISTEM PAKAR DIAGNOSIS HAMA DAN PENYAKIT TANAMAN JERUK LEMON DENGAN TEKNIK INFERENSI FORWARD CHAINING - Geri Reonaldo Sitepu; Murni Marbun (UPPM, 2018)
This research is a research on expert systems that can detect or diagnose diseases in lemon plants. Forward chaining inference technique is one of the methods found in the expert system that can search for the type of disease with the most symptoms in the input, so as to produce conclusions in the form ofdiseases of each disease. This system is built with Visual Basic 2010 and MySql applications as the database. The expert system that is built is able to diagnose the types of diseases found in lemon plants. Diseases that can be diagnosed include CPVD, tristeza, woody gall, blend, powdery mildew, scabies, fruit rot, and premature decay. The purpose of this application is to make it easier for farmers to get lemon juice to consult about lemon plants. The diagnosis of lemon juice is a type of disease, as well as a solution offered by an expert system. This expert system is built by applying or applying forward chaining inference techniques to the process.